Succinic anhydride and preparation method thereof
By using high-strength molybdenum disulfide/porous carbon support and non-precious metal nickel/copper catalytic centers and combined with hydrophobic compound modification, the problems of high precious metal usage and reduced catalyst activity in the prior art are solved, and the preparation and long-term production of low-cost and high-purity succinic anhydride are achieved.
Patent Information
- Application Number
- CN202411658133.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
In the prior art, when preparing succinic anhydride, the high amount of noble metal palladium is used to increase production costs and it is difficult to achieve long-term production.
High-strength molybdenum disulfide/porous carbon support is used as the catalyst support, combined with non-precious metal nickel and copper as the catalytic center, and the reaction conditions are regulated to achieve directional high-selective hydrogenation.
The preparation of low-cost and high-purity succinic anhydride is achieved, which avoids the problem of decreasing catalyst activity, ensures long-term production, and improves the purity and selectivity of the product.
Smart Images

Figure BDA0005142598950000081 
Figure FDA0005142598940000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of synthesis technology, and in particular relates to succinic anhydride and a preparation method thereof. Background Art
[0002] Succinic anhydride is an important organic synthesis intermediate and fine chemical raw material, widely used in food, surfactants, coatings, medicine, plastics and other fields. At present, the industrial methods for preparing succinic anhydride are succinic acid dehydration method and maleic anhydride catalytic hydrogenation method. The succinic acid dehydration method has a small production scale and low product quality; the maleic anhydride catalytic hydrogenation method has the advantages of simple process, easy operation, high product purity and few impurities, and is the most efficient production process.
[0003] Maleic anhydride molecules have one C=C bond and two C=O bonds. Under certain catalytic conditions, selective hydrogenation of the C=C bond can produce succinic anhydride; deep hydrogenation will produce γ-butyrolactone and tetrahydrofuran in turn. It can be seen that deep hydrogenation will reduce the selectivity of succinic anhydride. Therefore, controlling the hydrogenation reaction to stay at the C=C bond hydrogenation stage is the key point of maleic anhydride hydrogenation to produce succinic anhydride. In addition, the maleic anhydride catalytic hydrogenation system is an acidic system. Generally, acid-resistant systems will cause active center poisoning and cannot be produced for a long period of time.
[0004] Patents US1541210A and EP0691335A use precious metal palladium as the active center. Although the hydrogenation selectivity is high, the amount of precious metal used accounts for 3.0%-10.0% of the total weight of the catalyst, which greatly increases the production cost and is difficult to achieve industrialization.
[0005] Therefore, how to prepare high-purity succinic anhydride by low-cost, directional and highly selective hydrogenation is still an urgent problem to be solved and has great industrial value. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a succinic anhydride and a preparation method thereof, which adopts a high-strength molybdenum disulfide / porous carbon carrier to avoid the problem that the non-precious metal nickel and copper catalytic centers are lost to the product under pressurized hydrogenation conditions, thereby causing the catalyst activity to gradually decrease, thereby ensuring long-term production; in addition, the hydrophobic compound can make the hydrogenation product quickly desorb from the catalyst surface, and then by adjusting the reaction pressure and temperature, the degree of hydrogenation of maleic anhydride C=C and its two C=O bonds can be controlled to obtain the target product.
[0007] The first object of the present invention is to provide succinic anhydride, wherein the purity of the succinic anhydride is ≥99.85%, the succinic anhydride does not contain tetrahydrofuran, and the rest is impurities; the impurities include γ-butyrolactone, the content is ≤0.12%, and 1,4-butanediol, the content is ≤0.05%
[0008] The second object of the present invention is to provide succinic anhydride and a method for preparing the same, wherein a maleic anhydride solution and hydrogen are introduced into a reactor containing a supported catalyst to react, and then succinic anhydride is obtained by separation and purification;
[0009] The preparation method of the supported catalyst comprises the following steps:
[0010] S1, heat treating the asphalt and molybdenum disulfide to obtain a porous carbon / molybdenum disulfide carrier;
[0011] S2, dispersing a nickel precursor, a copper precursor and a hydrophobic compound in water to obtain a mixed solution; the structural formula of the hydrophobic compound is n≥6;
[0012] S3. The porous carbon / molybdenum disulfide carrier described in S1 is immersed in the mixed solution described in S2, and the supported catalyst is obtained through aging, drying and thermal reduction treatment.
[0013] In one embodiment of the present invention, in S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5-5:1; and the molybdenum disulfide is a nano-sheet structure with 5-20 layers.
[0014] In one embodiment of the present invention, in S1, the heat treatment is performed in an oxygen atmosphere at 200° C.-400° C. for 3 h-8 h.
[0015] In one embodiment of the present invention, in S2, the nickel precursor is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate; the copper precursor is selected from one or more of copper chloride, copper nitrate and copper sulfate.
[0016] In one embodiment of the present invention, in S3, the aging temperature is 50℃-80℃, and the time is 12h-16h; the drying temperature is 100℃-150℃, and the time is 10h-14h; the thermal reduction treatment is in a hydrogen atmosphere, heating to 160℃-200℃ at a rate of 10℃ / h-20℃ / h, and reducing for 6h-10h.
[0017] In one embodiment of the present invention, the nickel loading in the supported catalyst is 30wt%-60wt%, the copper loading is 5wt%-10wt%, and the hydrophobic compound loading is 0.01wt%-0.2wt%; the pore volume of the porous carbon / molybdenum disulfide carrier is 0.2mL / g-0.7mL / g, the particle size is 3mm-5mm, and the bulk density is 750kg / m 3 -1100kg / m 3The length of the cluster is 80nm-150nm, the width is 30nm-100nm, and the thickness is 10nm-30nm; the cluster is an active center composed of nickel, copper, and hydrophobic compounds supported on a porous carbon / molybdenum disulfide carrier.
[0018] In one embodiment of the present invention, the mass fraction of the maleic anhydride solution is 5wt%-30wt%; the solvent of the maleic anhydride solution is selected from one or more of tetrahydrofuran, γ-butyrolactone, ether, ethyl acetate, ethyl formate and methyl acetate; preferably, the solvent of the maleic anhydride solution is selected from tetrahydrofuran and / or γ-butyrolactone.
[0019] In one embodiment of the present invention, the reaction pressure is 1MPa-10MPa, the temperature is 25℃-100℃, and the air velocity is 0.6hr -1 -6.0hr -1 .
[0020] Preferably, the reaction pressure is 1 MPa-3 MPa, and the temperature is 40°C-70°C.
[0021] In one embodiment of the present invention, the flow rate ratio of the maleic anhydride solution and hydrogen is (0.1-5):(0.1-100).
[0022] The porous carbon / molybdenum disulfide carrier of the present invention, due to the layered structure characteristics of molybdenum disulfide, when the carrier is subjected to high temperature treatment, the asphalt will extend along the layered voids, and then undergo dehydration, deorganization and other processes at a certain temperature to form a layered carbon structure, which is firmly combined with molybdenum disulfide and produces a large number of pore structures, which is conducive to the dispersion of active metal components. At the same time, this composite carrier structure naturally has a very high mechanical strength, and it is easy to achieve a particle strength of ≥450N / cm, while the particle strength of traditional alumina is difficult to achieve this. The mechanical strength of alumina particles of commercial catalyst carriers can generally reach 100N / cm.
[0023] The technical solution of the present invention has the following advantages over the prior art:
[0024] (1) The supported catalyst of the present invention has a strength of more than 450 N / cm, and the metal is not easily lost during the reaction, which plays a key role in the synthesis of high-purity succinic anhydride.
[0025] (2) The supported catalyst described in the present invention uses nickel / copper non-precious metals as the catalytic center and porous carbon / molybdenum disulfide as the carrier. The nickel / copper non-precious metals are uniformly dispersed and supported in the ordered porous carbon / molybdenum disulfide carrier. The porous carbon / molybdenum disulfide carrier has a certain hydrogenation activity, which can promote the improvement of reaction activity, thereby reducing the reaction temperature, improving the reaction selectivity, and further improving the product purity.
[0026] (3) The supported catalyst of the present invention uses a hydrophobic compound as an additive. After the surface treatment with the hydrophobic compound, the supported catalyst surface has fewer C=O bond sites for adsorption, which can allow the product succinic anhydride to desorb from the supported catalyst surface as quickly as possible. On the one hand, it can accelerate the reaction speed, and on the other hand, it can avoid further reaction of the product on the catalyst surface, thereby achieving a maleic anhydride reaction conversion rate of up to 99.95%, and a product purity of more than 99.85%. It can also operate stably for a long period of time and can be used to prepare biodegradable polyesters such as polybutylene succinate or polybutylene succinate-adipate. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0028] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0029] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.
[0030] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0031] In the present invention, unless otherwise specified, the molybdenum disulfide used in the embodiments of the present invention is a nanosheet structure with 5-20 layers.
[0032] Example 1
[0033] The succinic anhydride and preparation method thereof of the present embodiment specifically comprise the following steps:
[0034] S1. Preparation of supported catalyst
[0035] S11. Preparation of porous carbon / molybdenum disulfide carrier: Asphalt and molybdenum disulfide were stirred and mixed in a mass ratio of 1:1, and heat treated at 300°C for 4 h under oxygen conditions to obtain a pore volume of 0.5 mL / g, a particle size of 5 mm, and a bulk density of 850 kg / m 3 A porous carbon / molybdenum disulfide support;
[0036] S12, preparation of a mixed solution: weigh 50.00 g of basic nickel carbonate, 9.16 g of copper nitrate, 159.5 mL of a 5 mol / L dilute nitric acid solution, 0.30 g of sodium dodecyl sulfate and 500.00 g of deionized water, and stir at 45° C. until all solids are dissolved to obtain a mixed solution;
[0037] S13, preparation of supported catalyst: the porous carbon / molybdenum disulfide support was immersed in the mixed solution, aged at 60°C for 14h under stirring, then dried at 120°C for 12h, finally loaded into tube arrays, heated to 200°C at a heating rate of 20°C / h under hydrogen conditions and reduced for 6h, to obtain a supported catalyst with a cluster length of about 125nm, a width of about 86nm, and a thickness of about 18nm;
[0038] S2. Preparation of Succinic Anhydride
[0039] S21, preparation of maleic anhydride solution: dissolving maleic anhydride in tetrahydrofuran to obtain a maleic anhydride solution with a mass fraction of 5 wt%;
[0040] S22. Preparation of succinic anhydride: Maleic anhydride solution and hydrogen were mixed at flow rates of 0.5 mL / min and 50 mL / min respectively and then continuously introduced into a 50 mL hydrogenation tubular reactor filled with a supported catalyst for reaction at a reaction temperature of 70°C, a reaction pressure of 1.9 MPa(A), and a space velocity of 0.6 hr -1 , and then continuously enters the distillation separation tower for separation and purification, the separation temperature is 140°C, the separation pressure is 50KPa(A), and the product is obtained.
[0041] Example 2
[0042] The process is basically the same as Example 1, except that during the preparation of the supported catalyst, basic nickel carbonate is replaced by nickel nitrate.
[0043] Example 3
[0044] The process is basically the same as Example 1, except that during the preparation of the supported catalyst, copper nitrate is replaced by copper chloride.
[0045] Example 4
[0046] The method is basically the same as Example 1, except that during the preparation of succinic anhydride, the 5wt% maleic anhydride solution is replaced with a 10wt% maleic anhydride solution.
[0047] Example 5
[0048] The method is basically the same as Example 1, except that in the preparation process of succinic anhydride, the solvent tetrahydrofuran of the maleic anhydride solution is replaced by the solvent γ-butyrolactone; the separation and purification conditions are a separation temperature of 140° C. and a separation pressure of 50 KPa (A) are replaced by a separation temperature of 160° C. and a separation pressure of 10 KPa (A).
[0049] Comparative Example 1
[0050] The process is basically the same as Example 1, except that copper nitrate is not added during the preparation of the supported catalyst.
[0051] Comparative Example 2
[0052] The method is basically the same as Example 1, except that sodium dodecyl sulfate is not added during the preparation of the supported catalyst.
[0053] Comparative Example 3
[0054] The method is basically the same as Example 1, except that copper nitrate and sodium dodecyl sulfate are not added during the preparation of the supported catalyst.
[0055] Comparative Example 4
[0056] The method is basically the same as Example 1, except that molybdenum disulfide is not added during the preparation of the supported catalyst.
[0057] Test Example 1
[0058] The strength test of the supported catalysts of Examples 1-5 and Comparative Example 4 was carried out according to the HG / T 2782 standard. The results are shown in Table 1:
[0059] Table 1
[0060] Sample Strength (N / cm) Example 1 450.6 Example 2 455.5 Example 3 455.8 Example 4 450.6 Example 5 450.6 Comparative Example 4 203.6
[0061] As can be seen from Table 1, the strength of the supported catalyst prepared in the example exceeds 450 N / cm. By combining high-strength molybdenum disulfide with porous carbon, the strength of the supported catalyst can be greatly improved. This can avoid the problem of non-precious metal nickel and copper catalytic centers being lost to the product under pressurized hydrogenation conditions, thereby causing the catalyst activity to gradually decrease, and ensure long-term production.
[0062] Test Example 2
[0063] The product purity and impurity content of Examples 1-5 and Comparative Examples 1-4 were tested by gas chromatography, using a gas chromatography column HP-5 (30m×320μm×0.25μm) and an FID detector; the column temperature conditions were an initial temperature of 60°C, a first-order termination temperature of 90°C, a heating rate of 15°C / min, and a hold time of 2min. The second-order termination temperature was 230°C, a heating rate of 10°C / min, an injection port temperature of 260°C, a split ratio of 100:1, an injection volume of 0.2μL, a hydrogen flow rate of 30mL / min, and a nitrogen flow rate of 25mL / min. Using acetone as the solvent, standard curves of maleic anhydride, succinic anhydride, tetrahydrofuran, γ-butyrolactone, and 1,4-butanediol were established. The results of the conversion rate (%) of maleic anhydride and the selectivity (%) of succinic anhydride during the continuous experiment of the hydrogenation process for 1000h are shown in Table 2:
[0064] Table 2
[0065] Sample Maleic anhydride Succinic anhydride Tetrahydrofuran γ-Butyrolactone 1,4-Butanediol Example 1 - 99.92 - 0.08 - Example 2 - 99.90 - 0.10 - Example 3 - 99.88 - 0.12 - Example 4 0.05 99.90 0.05 Example 5 - 99.85 0.10 0.05 Comparative Example 1 - 99.40 0.50 0.10 Comparative Example 2 5.00 95.00 Comparative Example 3 3.60 94.40 2.00 Comparative Example 4 20.00 80.00 - - -
[0066] It can be seen from Table 2 that the purity of succinic anhydride prepared in Example 1 is ≥99.85%, the residual content of maleic anhydride is ≤0.05%, and the content of γ-butyrolactone is ≤0.15%, indicating that the method of the present invention can prepare high-purity succinic anhydride.
[0067] Test Example 3
[0068] The products (succinic anhydride) of Examples 1-5 and Comparative Examples 1-4 were subjected to polymerization experimental evaluation, and the specific polymerization steps were as follows: 200.0 g of succinic anhydride and 252.0 g of 1,4-butanediol were added to a 1000 mL three-necked flask, and an esterification reaction was carried out at 180° C. When water was no longer distilled from the system, the esterification was completed, and then 0.39 g of tetrabutyl titanate catalyst was added, and the reaction temperature was 230° C. and 2.5 KPa (A) for a pre-condensation reaction for 2 hours. Finally, a high vacuum condensation reaction was carried out at 230° C. and 100 Pa (A) for 3 hours to prepare a polymer product. The polymer product was tested for melt index and color value. The melt index was tested using a melt index meter at a test temperature of 190°C and a test pressure of 2160g. The specific test was in accordance with GB / T 3682-2000. The hue was tested using the CIE1976L*a*b* color system test. The specific test was in accordance with 5.5.2 of GB / T14190-2008. The results are shown in Table 3:
[0069] Table 3
[0070]
[0071] As can be seen from Table 3, the high-purity succinic anhydride prepared by the method of the present invention can be used to prepare polybutylene succinate polyester materials with high viscosity (melt index <10 g / 10 min) and bright white color (L value >80, b value <7).
[0072] Obviously, the above embodiments are only examples for clear explanation and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
Claims
1. A succinic anhydride, characterized in that The purity of the succinic anhydride is ≥99.85%, tetrahydrofuran is not contained, and the rest are impurities; the impurities include gamma-butyrolactone, the content of which is ≤0.12%, and 1,4-butanediol, the content of which is ≤0.05%.
2. A method for preparing succinic anhydride as claimed in claim 1, characterized in that: A maleic anhydride solution and hydrogen are introduced into a reactor containing a supported catalyst to react, and then succinic anhydride is obtained by separation and purification; The preparation method of the supported catalyst comprises the following steps: S1, heat treating the asphalt and molybdenum disulfide to obtain a porous carbon / molybdenum disulfide carrier; S2, dispersing a nickel precursor, a copper precursor and a hydrophobic compound in water to obtain a mixed solution; the structural formula of the hydrophobic compound is n≥6; S3. The porous carbon / molybdenum disulfide carrier described in S1 is immersed in the mixed solution described in S2, and the supported catalyst is obtained through aging, drying and thermal reduction treatment.
3. The method for preparing succinic anhydride according to claim 2, characterized in that: In S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5-5:1; and the molybdenum disulfide is a nano-sheet structure with 5-20 layers.
4. The method for preparing succinic anhydride according to claim 2, characterized in that: In S1, the heat treatment is performed under an oxygen atmosphere at 200°C-400°C for 3h-8h.
5. The method for preparing succinic anhydride according to claim 2, characterized in that: In S2, the nickel precursor is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate; the copper precursor is selected from one or more of copper chloride, copper nitrate and copper sulfate.
6. The method for preparing succinic anhydride according to claim 2, characterized in that: In S3, the aging temperature is 50℃-80℃, and the time is 12h-16h; the drying temperature is 100℃-150℃, and the time is 10h-14h; the thermal reduction treatment is carried out in a hydrogen atmosphere, with the temperature being increased to 160℃-200℃ at a rate of 10℃ / h-20℃ / h, and the reduction is carried out for 6h-10h.
7. The method for preparing succinic anhydride according to claim 2, characterized in that: The nickel loading of the supported catalyst is 30wt%-60wt%, the copper loading is 5wt%-10wt%, and the hydrophobic compound loading is 0.01wt%-0.2wt%; the pore volume of the porous carbon / molybdenum disulfide carrier is 0.2mL / g-0.7mL / g, the particle size is 3mm-5mm, and the bulk density is 750kg / m 3 -1100kg / m 3 ; The length of the cluster is 80nm-150nm, the width is 30nm-100nm, and the thickness is 10nm-30nm.
8. The method for preparing succinic anhydride according to claim 2, characterized in that: The mass fraction of the maleic anhydride solution is 5wt%-30wt%; the solvent of the maleic anhydride solution is selected from one or more of tetrahydrofuran, γ-butyrolactone, ether, ethyl acetate, ethyl formate and methyl acetate.
9. The method for preparing succinic anhydride according to claim 2, characterized in that: The reaction pressure is 1MPa-10MPa, the temperature is 25℃-100℃, and the space velocity is 0.6hr -1 -6.0hr -1 .
10. The method for preparing succinic anhydride according to claim 2, characterized in that: The flow rate ratio of the maleic anhydride solution and hydrogen is (0.1-5):(0.1-100).
Citation Information
Patent Citations
Process for the preparation of succinic anhydride
EP0691335A1
Production technology for preparing high-purity succinic anhydride through direct hydrogenation of maleic anhydride
CN107253938A
Application of two-dimensional MoS2 catalyst in catalyzing selective hydrogenation of maleic anhydride to prepare succinic anhydride
CN112961130A
Production method of high-purity polymer-grade succinic anhydride
CN118702651A